1997
DOI: 10.1038/nbt1197-1261
|View full text |Cite
|
Sign up to set email alerts
|

Increased potency of an erythropoietin peptide mimetic through covalent dimerization

Abstract: We have synthesized a chemically defined, dimeric form of an erythropoietin mimetic peptide (EMP) that displays 100-fold increased affinity for the erythropoietin receptor (EPOR) and correspondingly elevated potency in cell-based assays and in mice. The dimeric EMP1 was synthesized using a C-terminal lysine residue as a branch point. A beta-alanine residue was coupled to the main-chain (alpha) amino group of the lysine residue in order to provide a pseudosymmetrical scaffold where both the side-chain and main-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(64 citation statements)
references
References 18 publications
0
62
0
2
Order By: Relevance
“…It would also be interesting to test combinations of peptides binding to A-and B-class Eph receptors involved in a particular pathological process, such as EphB4 and EphA2 in cancer (5,8,49,50). Finally, the affinity of the EphB receptorbinding peptides may be greatly increased by dimerization through a flexible linker (36,42,43). However, it is possible that the dimerized peptides may become agonists.…”
Section: Fig 5 Peptides As Ephb Receptor-targeting Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It would also be interesting to test combinations of peptides binding to A-and B-class Eph receptors involved in a particular pathological process, such as EphB4 and EphA2 in cancer (5,8,49,50). Finally, the affinity of the EphB receptorbinding peptides may be greatly increased by dimerization through a flexible linker (36,42,43). However, it is possible that the dimerized peptides may become agonists.…”
Section: Fig 5 Peptides As Ephb Receptor-targeting Agentsmentioning
confidence: 99%
“…Phage display is a powerful approach to identify competitive antagonists and ligand mimics, but the peptides isolated are typically of low affinity and often need to be optimized by further "affinity maturation" (29,30,39,40), introduction of conformational constraints (30,41), or cross-linking to increase valency (36,42,43). To optimize the TNYL peptide, we have used a different approach.…”
Section: Fig 5 Peptides As Ephb Receptor-targeting Agentsmentioning
confidence: 99%
“…The establishment of this proof of concept for NGF loop 1 along with the emerging role of peptidomimetics as a key intermediate-stage strategy in small molecule drug design (8, 26 -28) will contribute to rational screening and design programs for producing potent NGF small molecule mimetics with agonist activity. Our NGF dimeric peptidomimetic strategy has been further encouraged by the synthesis of small peptides mimicking the 34-kDa dimeric protein erythropoietin and the finding that erythropoietin receptor activation by peptidomi-metics also requires the dimeric form (30). These erythropoietin peptidomimetics have served as starting points for the design of erythropoietin small molecule compounds (31).…”
mentioning
confidence: 99%
“…19 It was found that the dimerization of 2 Epo mimetic peptides strongly increased their activity, though it remained inferior to that of native Epo. 20,21 The association of 2 Epo molecules obtained by either chemical cross-linking or recombinant DNA-mediated fusion of coding regions resulted in a more stable protein than the native monomer with an increased in vivo life span. 22,23 Based on evidence that the bridging of 2 adjacent Epo receptors triggers a conformational change that initiates signal transduction 24,25 and that high-and low-affinity sites for the Epo receptor are present on Epo, [26][27][28] we hypothesized that the fusing of 2 Epo molecules might confer an increase in intrinsic activity by providing 2 closely associated high-affinity domains.…”
Section: Introductionmentioning
confidence: 99%